Effects of cannabidiol on contractions and calcium signaling in rat ventricular myocytes. Issue 4 (April 2015) - Ali, Ramez M.; Al Kury, Lina T.; Yang, Keun-Hang Susan; Qureshi, Anwar; Rajesh, Mohanraj; Galadari, Sehamuddin; Shuba, Yaroslav M.; Howarth, Frank Christopher; Oz, Murat
Graphical abstract